Hit the ball duck - Alborough, Jez. (La Jolla, CA : Kane/Miller Book Publishers, 2006)
Duck and his friends drive out into the countryside to play a game of baseball, but things get stalled when Duck hits the ball into a tree.
Originally published: London: HarperCollins Children's, c2005.
Booklist.
Horn Book.
Kirkus Review.
1.9
K-3
Keywords: Animals -- Juvenile fiction; Ball games -- Juvenile fiction; Duck (Fictitious character : Alborough) -- Juvenile fiction; Humorous stories; Animals -- Fiction; Ball games -- Fiction; Ducks -- Fiction; Humorous stories; Stories in rhyme; Animals -- Fiction; Ball games -- Fiction; Ducks -- Fiction; Humorous fiction; Stories in rhyme